BIOTECHNOLOGY : DREAM OR REALITY ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
By diversifying the tools that researchers can use to select and reproduce both plants and animals, biotechnology offers new potential for improving agricultural production. The successful use of these sophisticated techniques for development,...